What's in a Name?: Changes and Challenges in One Hundred Years of Inayat Khan's (Inayati) Universal Sufism - Genn, Celia (Journal for the academic study of religion, 2013)
In 2010, the International Sufi Movement celebrated one hundred years of Hazrat Inayat Khan's Sufi Message in the West. This article draws attention to recent developments within Inayati Sufi groups and identifies how new tensions arising in relation to the religion of Islam pose challenges for the group's identity and future. Separating Sufism from the exoteric tradition of Islam was part of Inayat Khan's vision for the future of religion, though Inayati orders honour their origins in, and retain significant strands of the Chishtiyya Sufism of India. This article reveals a mix of tradition and innovation in the group's history, thought and practice, and a variety of stances toward both Islam and the designation Sufi'. Despite the tensions, this transnational Sufi community remains characterised by an inner core of disciplined ethical spiritual work directed toward self and God realisation, and an ecumenical vision of universal brother and sisterhood, that accommodates seekers from all backgrounds.